Disseminated tumor cells in the bone marrow of patients with operable primary breast cancer: prognostic impact in immunophenotypic subgroups and clinical implication for bisphosphonate treatment - Stefanovic, Stefan; Diel, Ingo J.; Sinn, Peter; Englert, Stefan; Hennigs, André; Mayer, Christine; Schott, Sarah; Wallwiener, Markus; Blumenstein, Maria; Golatta, Michael; Heil, Jörg; Rom, Joachim; et al. (Annals of surgical oncology, 2016)
Background Disseminated tumor cells (DTC) in the bone marrow (BM) of primary breast cancer (BC) patients are a promising surrogate marker of micrometastatic spread and an independent predictor of poor prognosis for disease-free survival (DFS) and overall survival (OS). The present study aims to analyze DTCs as an independent prognostic factor for DFS/OS in tumor biology and bisphosphonate treatment.MethodsA total of 504 patients with operable primary BC and a median observation time of 72.3 months [lower quartile (LQ) 58.1; upper quartile (UQ) 82.8] have been included. DTCs were detected via immunohistochemistry as MUC-1 positive cells in the BM of 59.13 % (298 of 504) of the patients. The immunophenotyping of cancer cells was achieved immunohistochemically as well.ResultsFor luminal A/B carcinoma patients, we observed a significant benefit of BM DTC negativity with respect to DFS (luminal A, P = 0.0498; luminal B, P = 0.0224). In triple-negative patients, DTC-negative BM was associated with a longer OS (P = 0.0326). In a multivariate Cox survival analysis relating to DFS and OS, the DTC status was identified as an independent prognostic factor for DFS in luminal A/B BC (P = 0.0071). A multivariate Cox survival analysis among DTC-positive patients with luminal immunophenotype showed bisphosphonate application (P = 0.0326) to be an independent prognostic factor for DFS.ConclusionsThe findings of our multivariate analyses reveal BM DTC positivity as an independent risk factor for DFS particularly in luminal A/B BC patients. This might be a novel criterion for the identification of candidates most likely to benefit from additional adjuvant therapy possibly including bisphosphonates.